Which resistance training method best improves running economy in elite marathon runners: a 16-week randomised controlled study - Behardien, Muhammed (Department of Human Biology, 2025)
Background: Concurrent training combines resistance and endurance exercises in a single program and has been linked to improvements in running economy (RE), running muscle power factors, and time trial performance. However, the mechanisms underpinning these improvements remain unclear. This study compared concurrent heavy-weight training (HWT) and reactive-strength (RST) to determine which leads to better running performance improvements and to investigate the underlying mechanisms and adaptation time-course. Methodology: This blocked, randomised controlled study tested participants (HWT = 8, RST = 8) three times over 12 weeks interspersed with two four-week resistance training blocks. Body composition, 1- rep-max (RM) Smith machine back squat, countermovement jump, squat jump, drop jump, running biomechanics, aerobic treadmill test, maximal anaerobic running test (MART), and 5km time trial (5kmTT) were measured. A linear mixed model analysis assessed the group-by-time interaction for each variable. Post-hoc pairwise analyses were run when applicable. Additionally, Pearson's correlation coefficient tested for significant relationships between all variables. Results: Concurrent training does not affect body composition and VO2max running biomechanics and RE. A main effect of time (p < 0.05) was evident for absolute and relative 1RM back squat, modified reactive strength index during the countermovement jump (RSImod), peak treadmill speed, as well as maximum velocity and maximum oxygen demand during the MART. There was a significant group-by-time interaction (p < 0.05) for relative 1RM back squat at mid-testing, CMJpower at post-testing, and the 5kmTT. The RST group improved their 5kmTT by 73.91seconds (95%CI: -130.59 – 17.24); p = 0.02) more than HWT. Only ∆RE measured at participant's training speed (r = 0.54, moderate; p = 0.048), and oxygen demand during the final lap of the MART (r = -0.621, strong; p = 0.02) significantly correlated with ∆5kmTT over the pre- to mid-testing period. Conclusion: Overall, RST was shown to superior to HWT in improving 5kmTT performance, and that concurrent training improvements continue to linearly increase over a 10-week period. Even though this study was not able to explain the mechanisms underpinning these concurrent training elicited running performance improvements, it still yielded valuable results. This study showed that by periodising an easy, low-cost, time-efficient, and low- intensity RST program into an athlete's schedule, one can significantly improve athletes' race finish times by more than a minute. Therefore, these findings provide athletes, coaches, and conditioning professionals with an RST-based concurrent training program that can effectively improve recreational distance running performance.